Ambulatory Arterial Stiffness Indexes in Cushing’s Syndrome - Battocchio, Marialberta; Rebellato, Andrea; Grillo, Andrea; Dassie, Francesca; Maffei, Pietro; Bernardi, Stella; Fabris, Bruno; Carretta, Renzo; Fallo, Francesco (Hormone and Metabolic Research, 2017)
Long-standing exposure to endogenous cortisol excess is associated with high cardiovascular risk. The aim of our study was to investigate arterial stiffness, which has been recognized as an independent predictor of adverse cardiovascular outcome, in a group of patients with Cushing’s syndrome. Twenty-four patients with Cushing’s syndrome (3 males, mean age 49±13 years; 20 pituitary-dependent Cushing’s disease and 4 adrenal adenoma) underwent 24-h ambulatory blood pressure monitoring (ABPM) and evaluation of cardiovascular risk factors. The Ambulatory Arterial Stiffness Index (AASI) and symmetric AASI (sAASI) were derived from ABPM tracings. Cushing patients were divided into 8 normotensive (NOR-CUSH) and 16 hypertensive (HYP-CUSH) patients, and were compared with 8 normotensive (NOR-CTR) and 16 hypertensive (HYP-CTR) control subjects, matched for demographic characteristics, 24-h ABPM and cardiometabolic risk factors. The AASI and sAASI indexes were significantly higher in Cushing patients than in controls, either in the normotensive (p=0.048 for AASI and p=0.013 for sAASI) or in the hypertensive (p=0.004 for AASI and p=0.046 for sAASI) group. No difference in metabolic parameters was observed between NOR-CUSH and NOR-CTR or between HYP-CUSH and HYP-CTR groups. AASI and sAASI were both correlated with urinary cortisol in patients with endogenous hypercortisolism (Spearman’s rho=0.40, p=0.05, and 0.61, p=0.003, respectively), while no correlation was found in controls. Both AASI and sAASI are increased in Cushing syndrome, independent of BP elevation, and may represent an additional cardiovascular risk factor in this disease. The role of excess cortisol in arterial stiffness has to be further clarified.
Keywords: arterial stiffness; ambulatory blood pressure monitoring; Cushing’s syndrome